2006
DOI: 10.1055/s-2006-925292
|View full text |Cite
|
Sign up to set email alerts
|

Klinische Anwendung einer Stimmprothese mit silberoxidhaltigem Ventil (Blom-Singer® Advantage) - Biofilmresistenz, Prothesenverweildauer und Indikation

Abstract: Using a voice prosthesis with a valve containing silver oxide can normalize and even increase the in-situ lifetime in patients with frequent changing procedures caused by fungal growth on the valve. Therefore we recommend the use of this type of voice prosthesis for those patients as reduction of costs and effort results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 13 publications
0
9
1
Order By: Relevance
“…Comparison with results for the Provox ActiValve (median 291 days, p  < 0.001), shows a markedly shorter device life which is in concordance with its lower valve opening pressure and price. The device life of the Blom-Singer Dual Valve in our study also seems to be somewhat lower than the device life reported in previous investigations with the Blom-Singer ® Advantage (Kress: mean 101, median 87 days, Leder: mean 118–168 days) [7, 8]. …”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…Comparison with results for the Provox ActiValve (median 291 days, p  < 0.001), shows a markedly shorter device life which is in concordance with its lower valve opening pressure and price. The device life of the Blom-Singer Dual Valve in our study also seems to be somewhat lower than the device life reported in previous investigations with the Blom-Singer ® Advantage (Kress: mean 101, median 87 days, Leder: mean 118–168 days) [7, 8]. …”
Section: Discussioncontrasting
confidence: 83%
“…Due to patient comfort, safety and economical aspects, in the past years, several voice prostheses with additional features intended to prolong device life have become available. The Blom-Singer Advantage with a valve flap containing 7 % of silveroxide for patients with premature device failure due to biofilm formation colonisation [7, 8] and the Blom-Singer Dual Valve that incorporates two valve flaps containing silveroxide in the shaft of the device (no clinical data are currently available for this device), and the Provox ActiValve in which the valve flap and valve seat are constructed out of fluoroplastic and valve flap closure is supported by magnets for patients with early device failure due to biofilm formation and/or underpressure in the oesophagus during swallowing and/or inhalation [9]. In addition to these design changes, newer voice prostheses (Blom-Singer Dual Valve, Provox Vega and ActiValve) have also been found to have more defined opening pressures, which may lead to differences in device life [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various attempts have been made to extend device lifetime and to improve material resistance of voice prostheses to yeasts and bacteria: surface treatments with active agents, alteration of surface properties by laser, and admixture of silver oxide into the silicone material 1–6. Various valve designs, such as the hinged valve flap (Provox 1, Provox 2, Provox Activalve), the slit valve type (Groningen Button), the tripod‐ball valve type (Voicemaster), and even valveless design (Nijdam) have been used in prosthesis construction.…”
mentioning
confidence: 99%
“…Blom and Singer developed advantage tracheoesophageal voice prosthesis with modified flanges and a valve flap that is covered with 7% silver oxide in order to avoid candida community. Leder et al and Kress et al evaluated a longer duration of those voice prosthesis in comparison to the classic Blom-Singer voice prostheses [168], [169]. …”
Section: Voice Prostheses and Their Applicationmentioning
confidence: 99%